Artifact reduction in free‐breathing, free‐running myocardial perfusion imaging with interleaved non‐selective RF excitations. Issue 2 (25th March 2021) - Haji‐Valizadeh, Hassan; Guo, Rui; Kucukseymen, Selcuk; Cai, Xiaoying; Rodriguez, Jennifer; Pierce, Patrick; Goddu, Beth; Manning, Warren; Nezafat, Reza
Abstract : Purpose: To reduce inflow and motion artifacts in free‐breathing, free‐running, steady‐state spoiled gradient echo T1 ‐weighted (SPGR) myocardial perfusion imaging. Method: Unsaturated spins from inflowing blood or out‐of‐plane motion cause flashing artifacts in free‐running SPGR myocardial perfusion. During free‐running SPGR, 1 non‐selective RF excitation was added after every 3 slice‐selective RF excitations to suppress inflow artifacts by forcing magnetization in neighboring regions to steady‐state. Bloch simulations and phantom experiments were performed to evaluate the impact of the flip angle and non‐selective RF frequency on inflowing spins and tissue contrast. Free‐running perfusion with ( n = 11) interleaved non‐selective RF or without ( n = 11) were studied in 22 subjects (age = 60.2 ± 14.3 years, 11 male). Perfusion images were graded on a 5‐point Likert scale for conspicuity of wall enhancement, inflow/motion artifact, and streaking artifact and compared using Wilcoxon sum‐rank testing. Result: Numeric simulation showed that 1 non‐selective RF excitation applied after every 3 slice‐selective RF excitations produced superior out‐of‐plane signal suppression compared to 1 non‐selective RF excitation applied after every 6 or 9 slice‐selective RF excitations. In vitro experiments showed that a 30° flip angle produced near‐optimal myocardial contrast. In vivo experiments demonstrated that the addition of interleaved non‐selective RF significantly ( P < .01) improved conspicuity of wall enhancement (mean score = 4.4 vs. 3.2) and reduced inflow/motion (mean score = 4.5 vs. 2.5) and streaking (mean score = 3.9 vs. 2.4) artifacts. Conclusion: Non‐selective RF excitations interleaved between slice‐selective excitations can reduce image artifacts in free‐breathing, ungated perfusion images. Further studies are warranted to assess the diagnostic accuracy of the proposed solution for evaluating myocardial ischemia.